5.Frequency of Metabolic Syndrome in Subfertile Female Population in Mosul (Iraqi Journal of Medical Sciences, 2019)
Background:Metabolic syndrome is associated with obesity, which is a common condition in subfertlie women population. For that reason, the infertile women will be more predisposed for cardiac diseases.Objective:To know the prevalence of the metabolic syndrome among subfertile women in Mosul, a city in the north of Iraq.Methods;Seventy subfertile females aged >17 years were selected randomly. Adult Treatment Panel-III (ATP-III) guidelines was used for diagnosing metabolic syndrome. The diagnosis was done if any three of the following were present: central obesity, raised triglycerides ?150?mg/dl, low high-density lipoprotein (HDL-C) cholesterol, blood pressure ?130/?85?mmHg, and diabetes or fasting serum glucose (FSG) ?100?mg/dl.Results:Metabolic syndrome was diagnosed in 16 (22.85%) women. The prevalence was 15.8% in the population younger than 30?years and 55.5% in ages more than 30?years. Fifty percent of women with class II obesity had metabolic syndrome. The most common abnormality was the abnormal waist circumference (100%). Patients having metabolic syndrome had three components of the syndrome and none had four or five components at the same time.Conclusion:The prevalence of metabolic syndrome is high among subfertile women. Focus of cardiovascular prevention should be undertaken for these subjects.Keywords:Metabolic syndrome, infertility, polycystic ovary syndrome, diabetes, obesityCitation: Jarjees YT, Hassan ZMA, Al Dabbagh EH. Frequency of metabolic syndrome in subfertile female population in Mosul. Iraqi JMS. 2019; 17(2): 120-125. doi: 10.22578/IJMS.17.2.5
Keywords: Metabolic syndrome; infertility; polycystic ovary syndrome; diabetes; obesity